Предмет: Математика,
автор: event1234578
- 2 (х + 3) – (- х – 2) = 3 (-х + 4) + 3(х – 5)
Ответы
Автор ответа:
0
-2х-6+х+2=-3х+12+3х-15
-х-4= -3
-х=1
х=-1
-х-4= -3
-х=1
х=-1
Автор ответа:
0
1,2 -2,6х-2-5,6х=-27,04
Автор ответа:
0
-8,2х= -27,04+2-1,2
Автор ответа:
0
-8,2х= -26,24
Автор ответа:
0
х=3,2
Автор ответа:
0
1)5,2 + 0,5 (х – 3) = 3 – 0,8 (х + 4)
2)0,3 (5х + 0,2) = -2,6 – (2,7х – 1,4)
2)0,3 (5х + 0,2) = -2,6 – (2,7х – 1,4)
Похожие вопросы
Предмет: Английский язык,
автор: nastasokol6233
Предмет: Английский язык,
автор: vikroria60
Предмет: Математика,
автор: razladintim9
Предмет: Физика,
автор: katyashevchenk2
Предмет: Алгебра,
автор: maksatabatov